Evaluation of clinical manifestation and risk factors of idiopathic granulomatous mastitis. (September 2021) - Pak, Haleh; Maghsoudi, Leila Haji; Soltanian, Ali; Jafarinia, Sepideh
Abstract: Background: Idiopathic granulomatous mastitis is a rare inflammatory breast pathology that, due to its rarity, remain challengeable for diagnosis. The disease has been suggested to have multiple etiologies. In this study the clinical manifestations and risk factors of idiopathic granulomatous mastitis (IGM) were assessed. Methods and materials: In this case-control study 30 cases with idiopathic granulomatous mastitis and 60 control subjects in clinical centers in (XXX) in 2020 were enrolled and clinical manifestations and risk factors were determined and compared across the groups. Results: The breast mass (40%), pain (23.3%), and discharge (36.7%) were significantly higher in idiopathic granulomatous mastitis versus control subjects (P = 0.001). Passive smoking was seen in 3 cases (10%) and none of the subjects in case and control groups, with significant difference (P = 0.035). Age, contraceptive use, tuberculosis, malignancy, family history, breastfeeding duration, child count, and gravid were significantly different between the groups (P > 0.05). Conclusions: Our study showed that breast mass, pain, and discharge are main clinical manifestations in idiopathic granulomatous mastitis cases and passive smoking is the main risk factor for this disease. The role of pregnancy, lactation, smoking and use of oral contraceptive in the etiology of the disease still remains unclear. Highlights: Idiopathic granulomatous mastitis is characterized has rare chronic inflammatory condition of breast. Idiopathic granulomatous mastitis is a rare inflammatory breast pathology. Our study showed that breast mass, pain, and discharge are main clinical manifestations. In idiopathic granulomatous mastitis cases and passive smoking is the main risk factor for this disease. The role of pregnancy, lactation, smoking and use of oral contraceptive in the etiology of the disease still remains unclear.